INTEGRASI AVENZA MAPS SEBAGAI MEDIA PEMBELAJARAN LAPANGAN UNTUK PENGUATAN KECERDASAN SPASIAL DAN LITERASI GEOSPASIAL MAHASISWA JURUSAN ILMU LINGKUNGAN FAKULTAS KEHUTANAN DAN ILMU LINGKUNGAN UNIVERSITAS HALU OLEO - Kete, Surya Cipta Ramadhan; Manan, Abdul; Hasani, Umar Ode; Fitriani, Dewi; Indriayani, Lies; Kasim, Safril; Bana, Sahindomi; Isabela, Isabela; Erif, La Ode Muhamad (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
The Training on Strengthening Spatial Intelligence and Geospatial Literacy Based on Avenza Maps was conducted to enhance the ability of students from the Department of Environmental Science, Faculty of Forestry and Environmental Science (FHIL), Halu Oleo University (UHO), in understanding and managing spatial data. The activity employed a participatory and experiential learning approach that integrates theory with field practice. Students were trained to use Avenza Maps for mapping, navigation, and creating digital thematic maps. The results showed improvements in students’ understanding of spatial concepts, technical skills, and positive attitudes toward the use of geospatial technology. The training proved effective in strengthening geospatial literacy, fostering environmental awareness, and supporting the enhancement of academic capacity based on spatial technology in higher education